2013
DOI: 10.1111/eip.12044
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis 101: evaluating a training programme for northern and remote youth mental health service providers

Abstract: The results about developing service partnerships and relationship with specialist services are encouraging for policy and service decision-makers to address mental health service needs in northern and remote areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Training agencies have begun to provide training remotely for some professionals in NL (e.g., mental health care providers; see Cheng, deRuiter, Howlett, Hanson, & Dewa, 2013). Cheng and colleagues (2013) demonstrated remote online training as an effective method of professional development, providing access to rural special education training and credentials (see also Larwood, 2005).…”
Section: Newfoundland and Labrador Contextmentioning
confidence: 99%
“…Training agencies have begun to provide training remotely for some professionals in NL (e.g., mental health care providers; see Cheng, deRuiter, Howlett, Hanson, & Dewa, 2013). Cheng and colleagues (2013) demonstrated remote online training as an effective method of professional development, providing access to rural special education training and credentials (see also Larwood, 2005).…”
Section: Newfoundland and Labrador Contextmentioning
confidence: 99%
“…In the other, there was an increase in the proportion of referrals made (from two to eight) and accepted (from zero to four) to an early intervention service following the training. It was noted, however, that these referrals were not made by participants who attended the training (Cheng et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A second paper by Cheng et al 2 The results demonstrated that the videoconference training intervention increased participants' familiarity and partnership with psychiatric services. However, when participants were followed up at nine months, their knowledge of schizophrenia was no different from baseline when comparing on site and videoconference educational resources.…”
Section: How Is Videoconferencing Used In Mental Health?mentioning
confidence: 96%